Avaliação da resistência ao desgaste e tenacidade do aço AISI M2 com tratamento criogênico - Leonardi, Luiz Felipe Stona (2019)
Rapid steels are widely used for manufacturing machining tools, subject to diferente efforts. In order to increase tool life, cryogenic treatments coupled with conventional treatments can provide numerous benefits, such as increased hardness, microhardness, wear and toughness. Recent studies have been carried out in the area in order to discover the best combination of treatments for a particular type of application. The present work aims to evaluate the wear resistance and toughness of the AISI M2 steel with cryogenic treatment. After the conventional treatment, three routes for cryogenics were studied: -120 ° C, -150 ° C and -180 ° C. The methodology used in the study was the experimental research, seeking correlation with the recent works of the area. The results indicated that all the cryogenic routes provided significant gains in hardness, microhardness and wear resistance.